Qualitative fieldwork to identify CSA practices preferred by women farmers in India, Kenya, and Uganda - Magalhaes, Marilia; Kawerau, Laura; Kweyu, Janerose; Pathak, Vishak (International Food Policy Research Institute, 2023)
Promoting the adoption of climate-smart agricultural (CSA) practices is an important step toward enhancing farmer resilience to climate change. Given the differences in the resilience capacities, operating space, and response options of men and women farmers, it is imperative to understand the gendered preferences for and constraints to their adoption of CSA practices. This policy brief summarizes qualitative research conducted in rural India, Kenya, and Uganda to identify CSA practices preferred by women and men farmers. The findings highlight the need for gender-responsive finance models and information channels to ensure that support to climate change adaptation does not further widen the gender gap in agricultural resources, agency, and achievement.